Pembatalan SK Pemberhentian Tidak Hormat Notaris oleh Pengadilan Akibat Kesalahan Kementerian Hukum dan HAM (Studi Kasus Putusan Nomor 294 K/TUN/2021) - Nasution, Reynaldi Yuliansyah; Somasir, Tetti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Notaries in carrying out their authority and duties are regulated by Law Number 2 of 2014. A notary can be dismissed by the Minister of Law and Human Rights if they commit a serious violation. A notary can file an objection and a cancellation lawsuit against the Dishonorary Dismissal Decree issued by the Ministry of Law and Human Rights as stated in the Jakarta State Administrative Court Decision Number 294 K/TUN/2021. Where the court subsequently revoked and annulled the Decree of the Minister of Law and Human Rights Number AHU.55.AH.02.04 of 2019. The issue in this research is to determine the accountability of the Minister of Law and Human Rights and to understand how to restore the reputation of notaries who have been harmed by the dishonorable dismissal by the Ministry of Law and Human Rights from the Notary position based on the annulment of the decree by the court as stated in decision Number 294 K/TUN/2021. Meanwhile, the research method used in this study is normative juridical, which employs secondary legal data and qualitative data analysis. And the theories used to analyze the issues in this research are Hans Kelsen's Theory of Responsibility, Philipus M. Hadjon's Theory of Legal Protection, and the general principles of good governance. The results of the research and discussion, as well as the conclusion, indicate that the decision of the Minister of Law and Human Rights has not met the principle of prudence based on the Judge's consideration, and it is the Minister's responsibility to revoke the decision that has been made and restore the Notary's status by reappointing them as a Notary in their original place as one of the efforts to restore the Notary's good name.